How equilibrium exchange rate misalignments influence on economic growth? Evidence for European countries - María del Carmen Ramos-Herrera (Economics: The Open-Access, Open-Assessment Journal, 2022)
The determination of the equilibrium real exchange rate is one of the most important issues in open economy since the policymakers are concerned about predicting and monitoring misalignments and they are usually associated with current account problems and currency crises. To the best of my knowledge, this is the first time a study provides empirical evidence on the impact of deviations from the long-run sustainable real exchange rate equilibrium on real economic growth rate applying panel ARDL model (pooled mean group, mean group and dynamic fixed effect estimators) for the 27 European countries during the 2000-2016 period. This study applies the EQCHANGE database developed by Couharde et al. (2017) to obtain the real effective exchange rate (REER) misalignments according to the behavioral equilibrium exchange rate approach for each country. One of the main objectives is to determine the relationship between REER misalignments and economic growth trying to differentiate between short- and long-run effects. To this purpose, a neoclassical growth model is considered controlling for several economic variables such as gross capital formation, degree of openness, human capital, inflation rate, and population rate.
Keywords: F43; F30; C23; O47; 330; economic growth; equilibrium real exchange rate; misalignments; panel ARDL